HUBUNGAN ANTARA PATRON DAN NELAYAN TRADISIONAL DI DESA KELARIK UTARA KECAMATAN BUNGURAN UTARA KABUPATEN NATUNA - Sidiawati "; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Every human being in his life relate to each other , the interdependence between communities with other communities . In communities can create social relations , social relations with the community we can maintain ties with other communities . So when we needed a rock from others will be easy . Both in the relationship of friendship , work and family relationships . It is very influential on our social relations in society . In the friendly relations , social relations is very important because with our good social relationship , the friendship will survive . In the cooperation of the relationship of economic and social relations between patron and traditional fishermen . Working relationships forged in order to mutually beneficial to each other , do not harm anyone .This research was conducted in the villages of North Kelarik North Bunguran Natuna . Population and sample are some people who worked as a patron ( toke ) and traditional fishermen . For patrons researchers took 20 people as the sample , 30 fishermen as a sample , and 1 person in the Department of Marine Natuna . Where the indicator in the relationship between patron and traditional fishermen is , fish trading relationship , relationship lending and borrowing , face to face relationship , the relationship dies visit , cooperation , solidarity relationships , and kinship . The most dominant influences relationship patron ( toke ) with traditional fishermen are cooperative relations , relations of solidarity visit death and relationships . They are maintaining social ties and economic ties , social relationships in the show in the form of the relationship of death , by giving material assistance , non-material , and for their economic relations remain a subscription and do not want to sell the catch with other people ring, and so they need each other .Keywords : Relationship Patron, Traditional Fishermen and communities